Triterpene composition and bioactivities of Centella asiatica - Hashim, Puziah; Sidek, Hamidah; Mohd Helan, Mohd Helme; Sabery, Aidawati; M. Palanisamy, Uma Devi; Adenan, Mohd Ilham (MDPI, 2011)
Leaves of Centella asiatica (Centella) were analysed for their triterpene composition and bioactivity such as collagen enhancement, antioxidant, anticellulite and UV protection capacity properties. Triterpenes of Centella were measured using HPLC-PAD on an Excil ODS 5 mm (C18) column for the simultaneous determination of asiatic acid, madecassic acid, asiaticoside and madecassoside. Centella was found to contain significant amounts of madecassoside (3.10 ± 4.58 mg/mL) and asiaticoside (1.97 ± 2.65 mg/mL), but was low in asiatic and madecassic acid. The highest collagen synthesis was found at 50 mg/mL of Centella extracts. The antioxidant activity of Centella (84%) was compared to grape seed extract (83%) and Vitamin C (88%). Its lipolytic activity was observed by the release of glycerol (115.9 µmol/L) at 0.02% concentration. Centella extracts exhibited similar UV protection effect to OMC at 10% concentration. In view of these results, the potential application of Centella in food and pharmaceutical industries is now widely open.